Desain Media Pembelajaran Interaktif berbasis Animasi pada Materi Perkembangbiakan Tumbuhan untuk Siswak Kelas IV Sekolah Dasar - Nadyla, Nadyla; Afifah, Mutiara Nur; Dwi, Resty Andini; Hendriatmi, Hendriatmi (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2024)
This research aims to explain the learning process by using interactive learning media, and also to improve the quality of student learning outcomes after using interactive learning media on Plant Breeding material for fourth grade students. The method used in this research is face-to-face using interactive learning media carried out in two cycles, where each cycle consists of planning, implementation, observation and reflection stages. The population in this study is all fourth-grade students, totaling five students. The results in this research before the action of displaying interactive learning media was carried out, student learning outcomes were 54.5; then after taking action in cycle I, student learning outcomes increased to 70 and in cycle II the results were a significant increase in student learning outcomes to 81. The conclusion in this research is that learning strategies using interactive learning media can improve student learning outcomes.